Vav3, a GEF for RhoA, Plays a Critical Role under High Glucose Conditions - Sha, Jie; Lee, Jung Ok; Kim, Nami; Lee, Soo Kyung; Kim, Ji Hae; Moon, Ji Wook; Kim, Su Jin; Lee, Hye Jeong; Choi, Jong-Il; Park, Sun Hwa; Kim, Hyeon Soo (Endocrinology and metabolism (Seoul), 2014)
The role of small GTPase molecules is poorly understood under high glucose conditions. We analyzed the expression pattern of Vav3 in skeletal muscle C2C12 cells under high glucose culture condition with reverse transcription-polymerase chain reaction and Western blot analysis. We also measured glucose uptake using isotope-labelled glucose. We showed that expression of Vav3 (a guanine nucleotide exchange factor for RhoA) increased. mRNA and protein levels in skeletal muscle C2C12 cells under high glucose conditions. The AMP-activated protein kinase (AMPK) activator AMPK agonist 5-aminoimidazole-4-carboxy-amide-1-d-ribofuranoside (AICAR) suppressed high glucose-induced Vav3 induction. In addition, exposure of cells to high glucose concentration increased the phosphorylation of PAK-1, a molecule downstream of RhoA. The phosphorylation of paxillin, a downstream molecule of PAK-1, was also increased by exposure to high glucose. Phosphorylation of these molecules was not observed in the presence of AICAR, indicating that AMPK is involved in the RhoA signal pathway under high glucose conditions. Knock down of Vav3 enhances metformin-mediated glucose uptake. Inhibition of AMPK blocked the increases of Vav3 knock down-induced glucose uptake. Metformin-mediated Glut4 translocation was also increased by Vav3 knock-down, suggesting that Vav3 is involved in metformin-mediated glucose uptake. These results demonstrate that Vav3 is involved in the process of metformin-mediated glucose regulation.